2002
DOI: 10.1097/00126334-200201010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Body Habitus Changes and Metabolic Alterations in Protease Inhibitor–Naive HIV-1–Infected Patients Treated With Two Nucleoside Reverse Transcriptase Inhibitors

Abstract: Treatment with NRTIs may be responsible for the same morphologic alterations as those observed in patients treated with PIs. Moreover, altered triglyceride levels are also frequently observed. The different timing of presentation and gender distribution of BHCs suggest that multiple pathogenetic mechanisms are involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
58
4
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 30 publications
3
58
4
3
Order By: Relevance
“…5% of patients* wz patients on non-PI-containing regimens, suggesting that NFV use may be more likely to be associated with accelerated atherosclerosis, and hence greater risk of coronary artery disease (CAD) [24]. The increase in lipids observed in the d4T/3TC/NFV group was greater than that observed in the COM/NFV group, confirming the results of earlier clinical trials that showed that d4T induces increases in cholesterol and triglycerides that are additional to those caused by concurrently administered PIs [25,26]. The value of TZV with respect to facilitating adherence and enhancing patient satisfaction over more complex HAART regimens has been reported elsewhere [27,28].…”
Section: Discussionsupporting
confidence: 71%
“…5% of patients* wz patients on non-PI-containing regimens, suggesting that NFV use may be more likely to be associated with accelerated atherosclerosis, and hence greater risk of coronary artery disease (CAD) [24]. The increase in lipids observed in the d4T/3TC/NFV group was greater than that observed in the COM/NFV group, confirming the results of earlier clinical trials that showed that d4T induces increases in cholesterol and triglycerides that are additional to those caused by concurrently administered PIs [25,26]. The value of TZV with respect to facilitating adherence and enhancing patient satisfaction over more complex HAART regimens has been reported elsewhere [27,28].…”
Section: Discussionsupporting
confidence: 71%
“…Several studies have found that stavudine was more involved in the occurrence of lipid derangements as compared with other NRTIs [22,23]. We found no difference in lipid profiles when participants on stavudine were compared to those on zidovudine.…”
Section: Discussioncontrasting
confidence: 63%
“…The advent of combined antiretroviral therapy (cART) increased survival, and resulted in the emergence of complications nonexistent or not perceived, until then, and thought to be drug-related adverse effects. These complications included body fat redistribution, increased fat mass, and changes in circulating lipids and glucose metabolism, all contributing to increased cardiovascular risk (CVR) (5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%